Качество обучения в вузе в концепции образовательного маркетинга - Дмитриев, В. Ю. (НТУ "ХПИ", 2014)
В статье рассматриваются вопросы применения образовательного маркетинга в системе высшего образования. Предлагается трактовка понятия "качество" в отношении товаров и услуг высшего образования. Анализируются понятия "качество образования" и "качество обучения", предлагается и обосновывается их различие в концепции маркетинга, даются общие определения. Подробно рассматриваются суть и содержание качественного обучения в вузе, предлагаются методы оценки качества обучения с учетом требований маркетинга. Сформулирована стратегическая цель маркетинговой деятельности вуза, предложены главные критерии, обеспечивающие достижение этой цели.

In the article the questions of application of the educational marketing in the system of higher education are examined. The conception of interpretation of "quality" in attitude toward commodities and services of higher education is offered. Concepts "Quality of education" and "quality of educating" are analysed, their distinction is offered and grounded in conception of marketing, general determinations are given. In detail essence and maintenance of the quality educating are examined in institution of higher learning, the methods of estimation of quality of educating are offered taking into account the requirements of marketing. The strategic aim of marketing activity of the institution of higher learning is set forth in the article, the main criteria of providing of the achievement of this aim are offered.
Quality education in high school in the concept of education marketing
Keywords: маркетинговая деятельность; рынок образовательных услуг; конкурентоспособность вуза; marketing activity; quality of educating; market of educational services